Kontribusi Kekuatan Otot Lengan, Otot Perut, Kelentukan Pergelangan Tangan, Koordinasi Mata dan Tangan, Power Otot Tungkai terhadap Ketepatan Open Smash Siswa Ekstrakulikuler Bolavoli Putri SMAN 1 Pademawu - Subaidi; Handayani, Heni Yuli; Purwoto, Septyaningrum Putri (SPRINTER: Jurnal Ilmu Olahraga, 2025)
The open smash is one of the most lethal attacking techniques in volleyball, executed with full force, sending the ball high and far into the air. Accuracy and good ball placement make it difficult for the opponent to return and give the team an advantage in organizing subsequent attacks. The purpose of this study was to determine the contribution of each of these physical components. The target group was 15 female volleyball extracurricular students at SMAN 1 Pademawu. While the data collection process is carried out by conducting tests on arm muscle strength (push-ups), abdominal muscles (sit-ups), wrist flexibility (goniometer), hand-eye coordination (grade mirror drawing), and leg muscle power (Jump Md) and open smash accuracy. (1) The results of the significance test state that the calculated r value is 0.652 > r table 0.514, with a contribution of 42.6%. (2) The results of the significance test state that the calculated r value is 0.616 > r table 0.514, with a contribution of 38.0%. (3) The results of the significance test state that the calculated r value is 0.728 > r table 0.514, with a contribution of 53.0%. (4) The results of the significance test state that the calculated r value is 0.699 > r table 0.514, with a contribution of 48.9%. (5) The results of the significance test state that the calculated r value is 0.739 > r table 0.514, with a contribution of 54.7%. (6) The results of the ANOVA state that the calculated F value = 19.464 > F table = 3.48, with a contribution of 91.5%.